Gender equality plans in Latin America and the Caibbean : road maps for development (United Nations SantiagoCL, 2017)
This study presents a review and analysis of the processes of drawing up the gender equality plans now in place in Latin American and Caribbean countries. It also addresses the link between machineries for the advancement of women and gender equality plans.
Keywords: GENDER EQUALITY